(untitled) (Trabalho & Educação, 2016)
This article examines the legal aspects and contributions of the Supervised Internship in Engineering for Engineers training, since, as an educational act, promotes the combination of knowledge (theory acquired in the educational environment) to do so (practice applied in the Marketplace work). The starting point for the analysis of legal references is the Decree no. 1002/67 which came to discipline the Curricular Supervised internship offering a contribution to improve workforce in the industrial and commercial sectors, but did not solve all questions referring to the practice of stages. The Law no. 6494 published in 1977 and Decree No. 87497 of 1982 are analyzed in sequence due to the relevance of the rules and guidelines of these two texts that regulated the training institute in the country for over thirty years. The last analyzed legal text is Law No. 11.788, published in 2008 and which became known as the New Law for internship because of implementations and adjustments which now require both the concession and in hiring interns to companies, institutions teaching and students / trainees. Unlike its predecessors, the new law introduces the stage as a complementary pedagogical action aimed at professional qualification aimed at students of various courses. In the current context, the Supervised Internship in Engineering links to learning the skills and knowledge required as a worker, professional activity, and development of the student as a citizen. Internship becomes a key link between the school and the professional environment so it contributes to the training, qualification, experience and practice of the Engineer. ___ Este artigo analisa os aspectos legais e as contribuições do Estágio Supervisionado em Engenharia para a formação de Engenheiros, uma vez que, como ato educativo, promove a combinação entre o saber (teoria adquirida no ambiente educacional) com o fazer (prática aplicada no mercado de trabalho). O ponto de partida para a análise das referências legais é a Portaria n. 1.002/67 que passou a disciplinar o Estágio Curricular Supervisionado oferecendo um aporte para uma melhor formação da mão de obra nos segmentos industrial e comercial, mas não resolvia todas as questões referentes à prática de estágios. A Lei n. 6.494, publicada em 1977, e o Decreto n. 87.497, de 1982, são analisados na sequência devido à relevância das regras e às orientações desses dois textos que regularam o instituto do estágio no país por mais de 30 anos. O último texto legal analisado é o da Lei n. 11.788, publicada em 2008 e que ficou conhecida como a Nova Lei do Estágio por causa das implementações e adequações que passou a exigir, tanto na concessão quanto na contratação de estagiários para empresas, instituições de ensino e estudantes/estagiários. Diferentemente das suas predecessoras, a Nova Lei apresenta o Estágio como ação pedagógica complementar que visa à qualificação profissional destinada a alunos de vários cursos. No contexto atual, o Estágio Supervisionado em Engenharia vincula-se à aprendizagem das competências e dos conhecimentos exigidos como trabalhador, na atividade profissional, e no desenvolvimento do aluno como cidadão. O Estágio torna-se um elo fundamental entre a escola e o ambiente profissional na medida em que contribui com a formação, a qualificação, a experiência e a prática do Engenheiro.